GROWTH AND PRODUCTIVITY OF SUGARCANE VARIETIES UNDER VARIOUS IRRIGATION LEVELS - Silva Costa, Cicero Teixeira; Cury Saad, Joao Carlos [UNESP]; Silva Junior, Helio Moreira da (Univ Fed Rural Semi-arido-ufersa, 2016)
This study evaluated the growth and agro-industrial productivity of sugarcane varieties subjected to different irrigation levels in the county of Penapolis - Sao Paulo, Brazil. The experimental design was a randomized block with a factorial arrangement of 2 x 7 (two cultivars of sugarcane: RB965902 and RB855453, at seven irrigation levels: L0 = 0%, L1 = 25%, L2 = 50%, L3 = 75%, L4 = 100%, L5 = 125%, and L6 = 150% of crop evapotranspiration - ETc) with four replicates. The irrigation system was a subsurface drip at a flow rate of 1.4 L h(-1). The variables evaluated were tillering, culm length, leaf area index (LAI), dry matter, and industrial productivity. The maximum number of plants per linear meter was 30 for variety RB965902 at 100% ETc, and 29 for variety RB855453 at 125% of ETc. Maximum tillering occurred at 120 and 150 days after planting (DAP) for RB965902 and RB855453, respectively. The maximum LAI of BR965902 was 9.57 at 210 DAP and 9.81 at 201 DAP for the RB855453 variety. The RB855453 variety produced an average of 178.93 t ha(-1) with irrigation and 164.81 t ha(-1) without, while the variety RB965902 produced 164.08 t ha(-1) and 154.61 t ha(-1) with and without irrigation, respectively. At harvest, the total recoverable sugars (TRS) were 129.62 kg t(-1) for RB965902 and 131.63 kg t(-1) for RB855443. The RB855453 variety produced on average 14.19 t ha(-1) more than the RB965902 variety.
Keywords: Saccharum officinarum; LAI; Culm length; TRS; Drip